Levantamento das classes de solo e aptidão agrícola como norteadores para o uso da terra no Projeto de Assentamento Bom Sucesso II, Flores de Goiás-GO - Queiroz, Paula Souza (2019)
The knowledge of soil properties is extremely important in relation to food production, since it is the one that will provide the water and nutrients necessary for the development of the plants. This knowledge may indicate, for example, whether a given crop will have satisfactory development, if there is need for correction, fertilization or irrigation, and whether there is a possibility of using machines. Thus, soil surveys can be used for land-use planning according to the scale of the property. The study area of this research is the Settlement Project (PA) Bom Sucesso II, located in Flores de Goiás / GO. Once it is a project of Agrarian Reform, it is necessary to evaluate the real conditions for investments in soil improvement by the beneficiaries. In this context, the objective of the research was to analyze the physical environment of the studied area, with emphasis on soil and land suitabilityof, the characterization of a profile of the settled population and the investigation of the possibility of developing family agriculture in the settlement according to this profile, the proposition of a redistribution of the Settlement Project's glebes according to the analyzes carried out, seeking to understand the importance of a previous soil study for the process of planning and implementation of Agrarian Reform Settlement Projects in Brazil, alongside its influence on the success of these projects. Field surveys, sample collection and analysis, soil classification and mapping were performed. The results were then interpreted to take into account not only the specific characteristics of the soil, but also the analysis of the physical environment and the yearnings of the beneficiaries residing in the area. From the interpretation, a map of simplified land suitability was drawn up and another one with a proposition for the redistribution of the PA lands. In the study area, Plinthsols class soils predominate, characterized by the presence of plinite and petroplintite, indicating oscillation of the water table and may represent impediments to drainage, root growth and mechanization. Soil analysis allowed its classification into three categories of agricultural aptitude, being areas with low restriction, areas with medium restriction and areas with high restriction. Areas of Medium and Low restriction correspond to 49% of the area, with soils suitable for agricultural production when respected the management techniques and the good use of the soil. 25.2% of the area is unviable for some type of production, either due to poor drainage by the near-surface impervious ferruginous concretion layer or due to sensitive environmental areas worthy of preservation. Another 25.8% of the area, although not feasible for production, is liable of a non-intensive form of use from natural pasture, without the removal of the native vegetation.